Craniopharyngioma presenting as a stroke mimic, a case report - Zachary Boivin; Chandler Ford; Andrew Franco (JEM Reports, 2023)
Background: Craniopharyngioma is a rare condition which can present with a multitude of symptoms from increased intracranial pressure, endocrine disorder, visual deficits, and hypothalamic dysfunction, making it difficult to diagnose. In this case, our patient presented with symptoms concerning for a stroke, creating diagnostic uncertainty. Case report: A 71-year-old male developed decreased grip strength in his right hand and word finding difficulties over a period of several hours, and upon arrival to the emergency department was triaged as a potential stroke. On initial imaging he appeared to have a hemorrhage in the area of the sella turcica. Subsequently, multidisciplinary input resulted in a preliminary diagnosis of craniopharyngioma. The patient's laboratory results raised concern for adrenal insufficiency, and the patient's vital sign abnormalities of bradycardia, hypotension, and hypothermia resolved with corticosteroids. The patient was discharged home after a brief hospital stay, and neurosurgery recommended outpatient follow up to excise the mass. Why should an emergency physician be aware of this: We could find no literature describing craniopharyngioma as a stroke mimic, and given the patient's initial presentation with right hand weakness and word finding difficulty, there was high concern for stroke. The patient's imaging showed what appeared to be an intracranial hemorrhage, further confounding the clinical picture. The patient's subsequent development of vital signs and laboratory results consistent with adrenal crisis helped us arrive at the final diagnosis. Emergency physicians should avoid anchoring bias in the treatment of patients with stroke-like symptoms and be familiar with the complex presentations of craniopharyngioma.